UK Finance: Fraud The Facts 2019. Issue 4 (April 2019) - Unknown
Abstract : Measured purely in terms of financial impact, fraud is one of the biggest forms of crime in the UK. In 2018, criminals stole £1.2bn, and they used technology – email, SMS texts, websites and even the humble telephone – to do it.